2021
DOI: 10.3390/app11125732
|View full text |Cite
|
Sign up to set email alerts
|

The Logopedic Evaluation of Adult Patients after Orthognathic Surgery

Abstract: Orthodontists correct dental malocclusion, but major facial skeleton deformations (skeletal malocclusion) are often subject to surgical correction. Several speech pathologies are associated with both of the occlusal anomalies mentioned above. The majority of articulation disorders and primary functions cannot be improved without skeletal correction. This study aimed to investigate the outcome of the multimodal and logopaedics treatment of Polish adults affected by skeletal malocclusion and speech-language path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
5
0
5
Order By: Relevance
“…The use of the FAMM flap is the ideal reconstructive technique for the reconstruction of medium-sized defects involving the floor of the mouth and up to one third of the ipsilateral tongue. Although it provides a limited width and requires a second-stage procedure in many patients, it offers many benefits: (1) it is a thin and pliable flap with a great arc of rotation and length; (2) it is a musculo-mucosal flap ideal for reconstruction of mucosal defects with the absence of hair; (3) it is a safe and reliable flap that withstands postoperative radiotherapy [1]; (4) it is easy to harvest; (5) it enables primary closure of the donor site under 3 cm; (6) it can be harvested simultaneously with neck dissection; (7) previous neck dissection and radiation therapy are not contraindications [11][12][13]; (8) it can be superiorly or inferiorly based depending on the defect to be reconstructed; (9) it can be used as a reconstructive technique simultaneously with immediate placement of osseointegrated implants for both aesthetic and functional rehabilitation. Common regional flaps such as supraclavicular, submental and pectoralis major flaps are other reconstructive techniques suitable for these defects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the FAMM flap is the ideal reconstructive technique for the reconstruction of medium-sized defects involving the floor of the mouth and up to one third of the ipsilateral tongue. Although it provides a limited width and requires a second-stage procedure in many patients, it offers many benefits: (1) it is a thin and pliable flap with a great arc of rotation and length; (2) it is a musculo-mucosal flap ideal for reconstruction of mucosal defects with the absence of hair; (3) it is a safe and reliable flap that withstands postoperative radiotherapy [1]; (4) it is easy to harvest; (5) it enables primary closure of the donor site under 3 cm; (6) it can be harvested simultaneously with neck dissection; (7) previous neck dissection and radiation therapy are not contraindications [11][12][13]; (8) it can be superiorly or inferiorly based depending on the defect to be reconstructed; (9) it can be used as a reconstructive technique simultaneously with immediate placement of osseointegrated implants for both aesthetic and functional rehabilitation. Common regional flaps such as supraclavicular, submental and pectoralis major flaps are other reconstructive techniques suitable for these defects.…”
Section: Discussionmentioning
confidence: 99%
“…An important topic to note would be the rehabilitation of speech articulation with a speech pathologist. Different studies have reported significant improvement in speech in different surgical specialties such as oral surgery and orthognathic surgery [7,8]. The interdisciplinarity of speech and its effectiveness in the treatment of oncologic patients require the cooperation of maxillofacial surgeons and speech pathologists to achieve the best possible result in terms of speech articulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research, in general, was about the relationship between malocclusion, speech and articulation disorders. Previous papers on the subject have published data on the impact of short frenulum on speech and logopaedic evaluation of adult patients after orthognathic surgery [10,11]. In the presented study, the materials and the method were extended and adjusted.…”
Section: Methodsmentioning
confidence: 99%
“…Lichnowska and Kozakiewicz [10,11] proved that abnormal functioning of the tongue caused by ankyloglossia affects speech in adult patients with skeletal deformities. Moreover, as mentioned above, the authors proved that in most cases, phonemes such as alveolar, dental and palatal are disturbed and such coincidence of malocclusion and speech disorders require surgical intervention to correct.…”
Section: Introductionmentioning
confidence: 99%